1988
DOI: 10.1254/jjp.46.237
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of monkey skeletal muscle arteries to vasoconstrictor substances before and after cold storage.

Abstract: Abstract-The stainless steel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…In this study, we demonstrated that the order of vasoconstrictor responses of alpha adrenoceptor agonists in isolated dog lingual arteries was almost the same as those shown to occur in dog mesenteric arteries (16), dog femoral arteries (17) and branches of the skeletal muscle area of dog femoral arteries (18). NE (a mixed alpha-1 and alpha-2 ago nist) and PE (an alpha-1 agonist) produced a strong vasoconstriction in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In this study, we demonstrated that the order of vasoconstrictor responses of alpha adrenoceptor agonists in isolated dog lingual arteries was almost the same as those shown to occur in dog mesenteric arteries (16), dog femoral arteries (17) and branches of the skeletal muscle area of dog femoral arteries (18). NE (a mixed alpha-1 and alpha-2 ago nist) and PE (an alpha-1 agonist) produced a strong vasoconstriction in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 61%
“…Compared with other blood vessels which have been investi gated in this laboratory using the same method, the lingual arteries from both species showed the lowest sensitivity to KCI. Sinano vic and Chiba (24) proposed that a relatively small vasoconstriction response to KCl in skeletal muscle arteries may indicate the rela tive resistance of the cell membrane to the KCl depolarizing effect and consequently, less Ca++ influx from the extracellular space, or/and an existence of relatively voltage in sensitive Ca++ channels.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cloni dine might produce a vasoconstriction mediated via a, adrenoceptors but not a2-adrenoceptors in the canine splenic artery, although clonidine is thought to be a selec tive a2-adrenoceptor agonist. Using the same method, we have reported that clonidine induces a vasoconstriction in the canine intermediate auricular artery via a2-adrenocep tors (17) and that clonidine does not constrict the canine lingual artery, femoral artery and mesenteric arteries, although there are abundant a,-adrenoceptors in these ar teries (18,22,23). A higher responsiveness of the splenic artery to clonidine suggests that the characteristics of a, adrenoceptors in the splenic artery are different from the ones in other arteries.…”
Section: Effects Of Vasoactive Agentsmentioning
confidence: 98%
“…Since Hongo and Chiba (4) introduced the cannula insertion method in pharmacological and physiological studies, effects of vasoactive substances on the canine intermediate auricular, femoral, mesenteric, ophthalmic, basilar, coronary and lingual arteries had been reported by the use of this method (8,(16)(17)(18)(19)(20)(21)(22)(23). Observations on vasoconstrictive responses to a-adrenoceptor agonists, ATP and histamine indicate that the distributions of adrenergic, purinergic and histaminergic receptors in different arteries are not always same (16,17,(19)(20)(21).…”
Section: Effects Of Vasoactive Agentsmentioning
confidence: 99%
See 1 more Smart Citation